Institutional and Empowerment Models of Integrated Zakāh Village in Jember - Mahardiyanto, Agus; Fathorrazi, Moehammad; Hardinawati, Lusiana Ulfa (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
Indonesia has a significant zakāh potential. However, the challenges  faced by zakāh management are related to the collection and distribution. This  research aims to analyze the institutional patterns and empowerment models of the Integrated Zakāh Village in Jember using the Participatory Rural Appraisal (PRA) theory. Using observations, a document study, Focused-Group Discussions (FGD), and in-depth interviews with the zakāh stakeholders, this research assesses the compatibility of the PRA theory in the development of Kampung Zakāh. This study finds that the obstacles in the Zakāh Village program are related to mustaḥiq's work ethics and enthusiasm. Among the aspects that need to be improved is the promotion of the program through social media to make it a massive community movement. Furthermore, this program empowers marginalized groups, including women, and encourages them to be independent. Abstrak:Indonesia memiliki potensi zakat yang signifikan. Namun, tantangan yang dihadapi oleh pengelola zakat di antaranya terkait dengan pengumpulan dan distribusi dana zakat. Penelitian ini bertujuan untuk menganalisis pola kelembagaan dan model pemberdayaan Kampung Zakat Terpadu Jember menggunakan teori Participatory Rural Appraisal. Dengan data observasi, studi dokumen, diskusi kelompok terfokus, dan wawancara mendalam dengan pemangku kepentingan zakat, penelitian ini menganalisis kesesuaian teori PRA dalam pengembangan Kampung Zakat. Studi ini menemukan bahwa hambatan dalam program Kampung Zakāh terkait dengan etos dan semangat kerja mustaḥiq. Di antara aspek yang perlu ditingkatkan adalah promosi program melalui media sosial untuk membuatnya menjadi gerakan masyarakat yang masif. Selanjutnya, program ini memberdayakan kelompok marjinal, termasuk perempuan, untuk menjadi mandiri.